Global Cleft Lip and Palate Outreach: A Google Trends Analysis. (April 2023) - Weissman, Joshua P; Reddy, Narainsai K; Shah, Nikhil D; Gosain, Arun K
Background : Understanding patient awareness of cleft lip and/or palate (CL/P) and evaluating demand for necessary procedures may serve to better target future efforts in global outreach. Methods : We utilized internet search query data from Google Trends for the terms: "cleft lip, " "cleft palate, " "cleft lip and palate, " "cleft surgery, " and "cleft repair" from January 2004 to January 2021. Relative search volumes (RSV) recorded for the top 5 highest displaying countries and top 3 available regions within those countries were compared against global outreach by Operation Smile and Smile Train, as measured by the number of patients treated. World Health Organization (WHO) indicators were used to validate the RSV values for each country and better understand the current infrastructure and need for cleft care in those countries. Results : Globally, there was an increase in RSV for the terms "cleft lip, " "cleft palate, " "cleft repair, " and "cleft surgery" between 2004 and 2021. For "cleft lip, " the countries with the highest displaying RSVs included: Ghana (100%), Zimbabwe (97%), Nepal (78%), the Philippines (64%), and Kenya (52%). Countries with high RSVs and moderate to high WHO indicators included Ghana, Kenya, India, Nigeria, and Zimbabwe. Countries with high RSVs and poor WHO indicators included Nepal and Pakistan. Some countries had specific regions with high search demand that are not currently targeted for global outreach. Conclusions : Using Google Trends' data may help find more feasible locations and targeted care for efforts in global outreach with better patient awareness and turnout where demand for CL/P is increasing.